The examination of in vitro photosensitizing efficacy of aloe-emodin loaded liposome following photodynamic therapy on melanoma cell lines - Martyna Nowak-Perlak; Marta Olszowy; Piotr Kupczyk; Dorota Wrześniok; Magdalena Zaremba-Czogalla; Roksana Dębicka; Alicja Makarec; Jerzy Gubernator; Piotr Ziółkowski; Marta Woźniak (Scientific Reports)
Abstract This study focused on investigating the enhanced photoactive properties of liposomal aloe-emodin for photodynamic treatment (PDT). Aloe-emodin (A-E) was encapsulated in liposomes by using the copper ion gradient method. This study aimed to highlight the function of naturally occurring photoactive plant-based derivatives in liposomal formulations as simple alternative photosensitizers (PS) for melanoma photodynamic therapy (PDT). Furthermore, we aimed to show that phototoxic chemicals loaded into liposomes are less cytotoxic than non-encapsulated molecules, which we used in our previous study. To assess the effectiveness of liposome aloe-emodin as a photosensitizer in PDT on melanoma cell lines, we performed cellular uptake by flow cytometry, MTT assay to measure the cytotoxicity of a natural compound, wound healing assay, ROS analysis by confocal microscopy, ROS analysis by flow cytometry, immunocytochemistry staining to measure the level of apoptotic proteins, and Real-Time PCR gene expression analysis. The melanoma cells showed increased phototoxicity after therapy compared to the normal cells in the MTT assay. Moreover, liposome aloe-emodin-based photodynamic therapy resulted in an increased ratio of apoptotic cells, increased ROS levels, and increased or decreased gene expression. This study also demonstrated that aloe-emodin encapsulated in liposomes significantly decreased melanoma cell motility following PDT treatment. In conclusion, our study provides evidence that aloe-emodin-mediated PDT exhibits potential for clinical development as a novel, safe, and effective photosensitizer for melanoma treatment.